Students’ perspectives on Remote Physiological Signals Acquisition Experiments - Barros, C. (2013)
Data acquisition of physiological signals is a very important issue since further health treatment depends on them. With recent developments in technology, new medical devices and new ways of monitoring and acquisition of physiological information emerge. So, not only medicals but also biomedical engineers must be prepared and aware of the characteristics and requirements needed. Following this tendency, this paper describes the developments of a remote lab for the study of biomedical and physiological systems in undergraduate and graduate level. The remote acquisition of ECG and body acceleration data was the experiments performed and evaluated by a group of biomedical engineering students. The experiments were conducted according to a protocol designed for the physiological data acquisition task. A pre and post questionnaires were applied to a group of students to obtain qualitative and quantitative evaluation to validate the remote experiment. The first results show a very positive attitude of the graduate students, motivating for further developments in this area.